Biosecurity risks to human food supply associated with plant-parasitic nematodes - Kantor, Camelia; Eisenback, Jonathan D.; Kantor, Mihail (Frontiers in Plant Science, 2024)
Biosecurity in agriculture is essential for preventing the introduction and spread of plant-parasitic nematodes (PPNs) which threaten global food security by reducing crop yields and facilitating disease spread. These risks are exacerbated by increased global trade and climate change, which may alter PPN distribution and activity, increasing their impact on agricultural systems.Addressing these challenges is vital to maintaining the integrity of the food supply chain. This review highlights significant advancements in managing PPN-related biosecurity risks within the food supply chain, particularly considering climate change's evolving influence. It discusses the PPN modes of transmission, factors increasing the risk of infestation, the impact of PPNs on food safety and security, and traditional and emerging approaches for detecting and managing these pests. Literature suggests that implementing advanced biosecurity measures could decrease PPN infestation rates by up to 70%, substantially reducing crop yield losses and bolstering food security. Notably, the adoption of modern detection and management techniques, (molecular diagnostics and integrated pest management) and emerging geospatial surveillance and analysis systems (spectral imaging, change-detection analysis) has shown greater effectiveness than traditional methods. These innovations offer promising avenues for enhancing crop health and securing the food supply chain against environmental shifts. The integration of these strategies is crucial, demonstrating the potential to transform biosecurity practices and sustain agricultural productivity in the face of changing climatic conditions. This analysis emphasizes the importance of adopting advanced measures to protect crop health and ensure food supply chain resilience, providing valuable insights for stakeholders across the agricultural sector.